2004
DOI: 10.1083/jcb.200312111
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiomyocytes fuse with surrounding noncardiomyocytes and reenter the cell cycle

Abstract: The concept of the plasticity or transdifferentiation of adult stem cells has been challenged by the phenomenon of cell fusion. In this work, we examined whether neonatal cardiomyocytes fuse with various somatic cells including endothelial cells, cardiac fibroblasts, bone marrow cells, and endothelial progenitor cells spontaneously in vitro. When cardiomyocytes were cocultured with endothelial cells or cardiac fibroblasts, they fused and showed phenotypes of cardiomyocytes. Furthermore, cardiomyocytes reentere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 53 publications
(75 reference statements)
5
82
1
2
Order By: Relevance
“…In short, enhanced green fluorescent protein (EGFP)-labeled BM-MSCs were cocultured with murine cardiomyocytes (see detail in supporting information Material and Methods). In this system, the incidence of cell fusion was around 0.3% [8,9,18] and the evidence of cell fusion-independent cardiomyogenesis was extensively shown in the previous study [5,8,9,11]. In our pilot study, we have confirmed that the incidence of cell fusion was not affected by pioglitazone (0.2%).…”
Section: Cardiomyogenic Induction and Chemical Agentssupporting
confidence: 75%
“…In short, enhanced green fluorescent protein (EGFP)-labeled BM-MSCs were cocultured with murine cardiomyocytes (see detail in supporting information Material and Methods). In this system, the incidence of cell fusion was around 0.3% [8,9,18] and the evidence of cell fusion-independent cardiomyogenesis was extensively shown in the previous study [5,8,9,11]. In our pilot study, we have confirmed that the incidence of cell fusion was not affected by pioglitazone (0.2%).…”
Section: Cardiomyogenic Induction and Chemical Agentssupporting
confidence: 75%
“…Early trials of cardiac repair and regeneration via transplantation of bone marrow-derived stem/progenitor cells have given mixed and modest results (for review see 37 ), indicating that a better understanding of the relevant cell biology is required to provide a consistently effective therapeutic option for stem cell-based regenerative treatments in the heart. The presence of resident eCSCs in the adult heart, including human, has been determined by several groups 2,4,6,[8][9][10]12,14,17,[38][39][40][41][42] . These cells can be isolated and propagated in vitro to produce large numbers of cells without reaching growth arrest or their being a change in cell characteristic.…”
Section: Characterisation Of Ecscsmentioning
confidence: 99%
“…As a result, transplanted stem cells may express the cardiac phenotype and re-enter the cell cycle, which may contribute to myocardial regeneration. This has been proved in an in vitro study in which cardiomyocytes could fuse with endothelial cells, cardiac fibroblasts and bone marrow cells, and the fused cells could re-enter the cell cycle (55). On the other hand, genes of the recipient cell may also be reprogrammed and their expression may be activated or inactivated.…”
Section: Reprinted From Reference 56 With Permissionmentioning
confidence: 91%